6x+35+9x=15(x+2)-25

Simple and best practice solution for 6x+35+9x=15(x+2)-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+35+9x=15(x+2)-25 equation:


Simplifying
6x + 35 + 9x = 15(x + 2) + -25

Reorder the terms:
35 + 6x + 9x = 15(x + 2) + -25

Combine like terms: 6x + 9x = 15x
35 + 15x = 15(x + 2) + -25

Reorder the terms:
35 + 15x = 15(2 + x) + -25
35 + 15x = (2 * 15 + x * 15) + -25
35 + 15x = (30 + 15x) + -25

Reorder the terms:
35 + 15x = 30 + -25 + 15x

Combine like terms: 30 + -25 = 5
35 + 15x = 5 + 15x

Add '-15x' to each side of the equation.
35 + 15x + -15x = 5 + 15x + -15x

Combine like terms: 15x + -15x = 0
35 + 0 = 5 + 15x + -15x
35 = 5 + 15x + -15x

Combine like terms: 15x + -15x = 0
35 = 5 + 0
35 = 5

Solving
35 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| y+34=19 | | 3-9x=84 | | 5y+12-5=22 | | 2(-x+8)=24 | | 2x^2+162=0 | | 6(x+2)=2(3x+8)-4 | | 3x+4-5x-14=10 | | 7d-4d-4d-6=2d | | 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 |

Equations solver categories